Response of Wheat to Cycocei (CCC) Application - II. Effects of nitrogen level and CCC concentration on yield components of dwarf and tall wheat (triticum aestivum). - EL-SHARKAWY, M. A.; SGAIER, K.; RAMADAN, M. M. (The Libyan Journal of Agriculture, 2023)
The effect of nitrogen level at the rate of 40, 80, and 120 kg N/ha and the foliar spray of the growth retardant CCC at the rate of 0.0, 2.5 and 6.0 kg a.i./ha on grain yield and its components were studied using the short-straw variety ‘sidi misri 1’ and the tall-straw variety ‘florence aurora’. Nitrogen application at 80 and 120 kg N/ha significantly increased grain yield (44 and 23%) and number of grains per spike (14.3 and 8%) of ‘sidi misri 1’. Grain size was significantly decreased (5.7 %) only with 80 kg N/ha. Slight, but not significant, increase of number of tillers and weight of grains/spike was found due to nitrogen application. Cycocel application at the rate of 2.5 and 6.0 kg a.i./ha increased grain yield of‘sidi misri 1’ by 14% and 21 %, respectively. Number of grains/ spike was significantly increased (10% and 6%) by CCC treatments; whereas grain size was significantly decreased (7.8% and 5.8%). Number of tillers and weight of grains/ spike were slightly increased by CCC treatments. With the tall-straw variety ‘florence aurora’, no significant increase in grain yield due to nitrogen and CCC treatments was observed except at 80 kg N/ha (there was 24 % increase). The number of tillers, the number of grains/spike, weight of grains/spike and the grain size were not significantly affected by nitrogen application with the only excep-tion of 8% significant increase in number of grains/spike at 120 kg N/ha. No significant response to CCC treatments was observed in regard to grain yield, number of tillers, number of grains/spike, weight of grains/spike and size of grain. Only at 2.5 a.i. CCC/ha the grain size of ‘florence aurora’ was significantly reduced by 4 %.